The outcome of patients with severe and severe‐complicated Clostridium difficile infection treated with tigecycline combination therapy: a retrospective observational study. Issue 6 (12th June 2018) - Bishop, Emma J.; Tiruvoipati, Ravindranath; Metcalfe, Julie; Marshall, Catherine; Botha, John; Kelley, Peter G.
Abstract: Background: Tigecycline is a third‐line therapy for severe Clostridium difficile infection (CDI) in Australasian guidelines. Differences in strain types make it difficult to extrapolate international tigecycline efficacy data with combination or monotherapy to Australian practice, where experience is limited. Aim: To evaluate the efficacy and adverse effects associated with tigecycline combination therapy for severe and severe‐complicated CDI in an Australian healthcare setting. Methods: This was a retrospective observational study at a metropolitan university‐affiliated hospital. All patients between February 2013 and October 2016 treated with adjunctive intravenous tigecycline for >48 h for severe or severe‐complicated CDI were included. Tigecycline was given in addition to oral vancomycin ± intravenous metronidazole. The primary outcome was all‐cause mortality at 30 days from start of tigecycline combination therapy. Secondary outcomes included clinical cure, colectomy, adverse events and recurrence rates. Results: Thirteen patients with median age of 61 years had severe ( n = 9) or severe‐complicated ( n = 4) CDI at tigecycline commencement. In 92% of patients, tigecycline started within 48 h after in‐hospital CDI treatment, for median duration of 9 days. All‐cause mortality at 30 days was 8% with no mortality in severe CDI and 25% (1/4) in patients with severe‐complicated fulminant CDI, comparing favourably with historical rates of 9–38% and 30–80% in similar respective groups. Clinical cure was achieved in 77% of cases. There were no colectomies and one attributable tigecycline adverse reaction. Conclusions: Tigecycline appears safe and effective as a part of combination therapy in severe CDI, and may be given earlier and for shorter durations than in current guidelines.